The role of electronic-based monitoring and evaluation systems (e-pelaporan) in organizational performance reporting at LIPI in 2018-2020 - Mai Damai Ria; Farham Harvianto (Monas: Jurnal Inovasi Aparatur, 2023)
Monitoring and evaluation is a means to monitor the use of public funds and at the same time monitor the performance of institutions to create a transparent and accountable bureaucracy (good governance). So far, monitoring and evaluation in LIPI has been carried out using a manual system through the exchange of documents. However, there are often difficulties in technical implementation due to the many and varied numbers of activities that must be monitored. In addition, LIPI has a broad scope of activities and work unit locations spread across various regions in Indonesia. Meanwhile, monitoring and evaluation is a joint work with a certain time limit, which requires the cooperation and involvement of various parties, especially the implementers of the activities. LIPI has built an electronic-based monitoring and evaluation system, e-pelaporan. The system was created to remove obstacles to the manual system and to respond to the demands of modernizing the administrative system in order to create good governance. This paper examines the use of these electronic systems to support performance monitoring and reporting at LIPI. A good performance monitoring and reporting system can increase the transparency and accountability of LIPI's performance so as to support the achievement of good governance. The method of analysis uses descriptive analysis with a qualitative approach based on the results of interviews and supporting documents. Data sources are primary data from system implementers and secondary data from relevant documents. It can be concluded that e-pelaporan makes it easier to collect, verify, and validate performance achievement data so that the time required is shorter. E-pelaporan can also bridge macro performance monitoring in institutions with performance monitoring at a more micro level in work units and individuals. Institutional accountability has also increased with the availability of an electronic-based monitoring and evaluation system that displays performance information in a concise and easy-to-read manner. E-pelaporan requires the collaboration of various parties from different work units, namely the Civitas as an individual, the Work Unit as an institution, and the Planning and Finance Bureau.